The Implementation of Social Protection Policies for Female Workers of PT. X’s Maternity Rights - Nilamsari, Wati; Rahayu, Ety; Fawzi, Indra Lestari; Laksmono, Bambang Shergi (International Journal Labs, 2023)
ackground: Maternity protection gives women the right to carry out their biological roles, including breastfeeding their children to improve the health of newborn children so that a healthy generation will grow up which is an asset of the nation, while female workers/laborers can continue to contribute to economic growth. Aim: The purpose of this study is to describe and analyze the implementation of social protection policies for the fulfillment of maternity rights of female workers in PT. X in South Tangerang City, Indonesia. Method: This research uses a qualitative approach with a descriptive method. The technique of taking research informants used purposive sampling techniques. The data analysis of this study starts from (1) collecting, selecting and compiling data, (2) providing emotional records and selecting data, (3) organizing and reducing data, (4) coding processes to describe settings, people, categories and themes analyzed, and (5) interpreting or interpreting data. Findings: The protection provided is no different from that of male workers, only with a special type of health service for women during pregnancy to childbirth. This budget for social protection is a corporate obligation and is handledjointly between the company and workers as stipulated in the BPJS Law. In addition to insurance, there is also social protection in the form of social assistance for workers, including scholarship assistance for children of outstanding workers, financial assistance for grief if the worker and his family members die, a one-year Umrah program for 2 selected people whose costs are fully borne by the employer.